Clinical characteristics and potential biomarkers of thyroid and pituitary immune-related adverse events - Tomoko Kobayashi; Shintaro Iwama; Hiroshi Arima (Endocrine Journal)
Immune checkpoint inhibitors (ICIs) can cause immune-related adverse events (irAEs) in several organs including endocrine glands. Among endocrine irAEs, thyroid and pituitary irAEs are frequently observed, followed by primary adrenal insufficiency, insulin-dependent diabetes mellitus, and hypoparathyroidism. These conditions could lead to life-threatening consequences, such as adrenal crisis and diabetic ketoacidosis. On the other hand, several types of irAEs including thyroid and pituitary irAEs are reported to be associated with better overall survival. Therefore, it is important to understand and manage endocrine irAEs, which differ depending on the ICI regimen used. In this review, we describe the clinical features, potential biomarkers, management strategies, and possible mechanisms of thyroid and pituitary irAEs.